Selection of Online Sales Platforms for MSMEs using the OCRA Method with ROC Weighting - Bagus Kusuma Wijaya; I Gede Iwan Sudipa; Devi Valentino Waas; Putu Praba Santika (Journal of Intelligent Decision Support System (IDSS), 2022)
MSMEs are required to utilize technology to facilitate sales transactions. Multiple online sales platforms have been made available, but they must be adapted to the needs of MSMEs. The objective of this research is to apply decision support techniques using the Competitiveness Rating Analysis (OCRA) method in the final ranking process combined with the Rank Order Centroid (ROC) weighting technique, with the resulting weight value based on the priority order of the criteria, to assist MSMEs in determining online sales platforms. The research data employs six evaluation criteria: application usability (C1), transaction features completeness (C2), personal data security (C3), simplicity of payment process (C4), ease of delivery process (C5), and partner service fee providing (C6). The selection process conducted on 5 alternative online sales platforms that are widely used by MSMEs, resulting in the ranking of the best alternative online sales platforms: Tokopedia with a value of 0.423, followed by Shoope with a value of 0.207, Instagram with a value of 0.121, Facebook marketplace with a value of 0.109, and WhatsApp as the final ranking order. Identifying the online sales platform can aid MSMEs in determining the most suitable sales platform for promoting greater sales and facilitating transaction processes.